Maritime order and the law in East Asia - Houlden, Gordon; Hong, Nong (Routledge/Taylor & Francis Group, 2018)
Providing an overview of the key maritime disputes occurring in the Asia Pacific, it examines case studies from a selection of representative countries to consider how these conflicts of interest reflect their respective national interests, and the wider issues that these interpretations have created in relation to navigation regimes, maritime entitlement, boundary delimitation and dispute settlement.